Fair play and skiing: Issues and controversies - Loland, S. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
The paper presents a systematic interpretation of fair play in sport (Loland 2002), and discusses some key implications for skiing.